Advances in the Supramolecular Chemistry of Tetracoordinate Boron-Containing Organic Molecules into Organogels and Mesogens - Shah, Sanchita; Marandi, Parvati; Neelakandan, P. P. (Frontiers in Chemistry, 2021)
Boron-containing organic compounds are well accepted as a class of compounds having excellent photophysical properties. In addition to the unique photophysical properties, the ease of synthesis and structural robustness make tetracoordinate boron complexes ideal for a variety of applications. While significant light has been thrown on their luminescence properties, there is no collective attention to their supramolecular chemistry. In this mini review, we discuss the progress made in the supramolecular chemistry of these compounds which includes their utility as building blocks for liquid crystalline materials and gels largely driven by various non-covalent interactions like H- bonding, CH-π interactions, BF- π interactions and Van der Waals forces. The organoboron compounds presented here are prepared from easy-to-synthesize chelating units such as imines, diiminates, ketoiminates and diketonates. Moreover, the presence of heteroatoms such as nitrogen, oxygen and sulfur, and the presence of aromatic rings facilitate non-covalent interactions which not only favor their formation but also helps to stabilize the self-assembled structures.